A Cursory View on Women in Constituent Assembly - Dr. Vanthangpui Khobung; Dr. Savita Sagar (Pandian Journal of Women's Studies)
This paper explores the critical yet often discounted role of women in India's Constituent Assembly, which laid the foundation for its democratic governance. Despite the inclusion of 15 women members—such as Sarojini Naidu and Vijay Laxmi Pandit—historical narratives frequently neglect their contributions, focusing more on their male counterparts. The study highlights these women’s diverse backgrounds and their multifaceted engagements in areas like freedom fighting, law, reform, and politics. It sought to fill the gap in constitutional history by showcasing their significant roles in legislative processes and social causes, advocating for gender diversity in nation-building. By raising awareness about their contributions and the issues they championed during the Assembly debates, the paper seeks to inspire contemporary readers to appreciate the importance of women's participation in society and to motivate them towards active involvement in national development.